1987
DOI: 10.1037/h0085712
|View full text |Cite
|
Sign up to set email alerts
|

A validation study of the Harvey Impostor Phenomenon Scale.

Abstract: This article examines the construct validity of the impostor phenomenon, as measured by the Harvey Impostor Phenomenon Scale (HIPS). A factor analysis was performed on the fourteen scale items, and the results revealed that three factors accounted for 54.7% of the variance. The six items loading into the largest of these factors identify it as an "impostor" factor, whereas the remaining two factors corresponded to feelings of unworthiness and inadequacy. The results point to the potential usefulness of the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 4 publications
1
35
0
2
Order By: Relevance
“…Furthermore, Edwards et al reported an alpha reliability for the total score of .34 yet argued for acceptable alpha levels for each of the three retained components (.81, .71, and .65, respectively). Ultimately, Edwards et al (1987) concluded that their study provides strong evidence for the validity of the Harvey IP Scale; yet this conclusion is not supported based on their own criteria of simple structure.…”
Section: Previous Psychometric Evidencementioning
confidence: 95%
See 4 more Smart Citations
“…Furthermore, Edwards et al reported an alpha reliability for the total score of .34 yet argued for acceptable alpha levels for each of the three retained components (.81, .71, and .65, respectively). Ultimately, Edwards et al (1987) concluded that their study provides strong evidence for the validity of the Harvey IP Scale; yet this conclusion is not supported based on their own criteria of simple structure.…”
Section: Previous Psychometric Evidencementioning
confidence: 95%
“…Gorsuch, 1983). More specifically, Edwards et al (1987) reported dual coefficient loadings on two items (Items 1 and 14, respectively) and no salient loadings for Item 12. Furthermore, Edwards et al reported an alpha reliability for the total score of .34 yet argued for acceptable alpha levels for each of the three retained components (.81, .71, and .65, respectively).…”
Section: Previous Psychometric Evidencementioning
confidence: 96%
See 3 more Smart Citations